Modeling of dispersion engineered chalcogenide rib waveguide for ultraflat mid-infrared supercontinuum generation in all-normal dispersion regime - Ahmad, Harith; Karim, Mohammad Rezaul; Rahman, B.M. Azizur (Springer, 2018)
A rigorous numerical investigation has been carried out through dispersion engineering of chalcogenide rib waveguide for near-infrared to mid-infrared ultraflat broadband supercontinuum generation in all-normal group-velocity dispersion regime. We propose a novel design of a 1-cm-long air-clad rib waveguide which is made from Ge 11.5 As 24 Se 64.5 chalcogenide glass as the core with either silica or Ge 11.5 As 24 S 64.5 chalcogenide glass as a lower cladding separately. A broadband ultraflat supercontinuum spanning from 1300 to 1900 nm could be generated when pumped at 1.55 μ m with a low input peak power of 100 W. Shifting the pump to 2 μ m , the supercontinuum spectra extended in the mid-infrared region up to 3400 nm with a moderate-input peak power of 500 W. To achieve further extension in mid-infrared, we excite our optimized rib waveguide in both the anomalous and all-normal dispersion pumping regions at 3.1 μ m with a largest input peak power of 3 kW. In the case of anomalous dispersion region pumping, numerical analysis shows that supercontinuum spectrum can be extended in the mid-infrared up to 10 μ m , although this contains high spectral amplitude fluctuations over the entire bandwidth which limits the supercontinuum sources in the field of high precision measurement applications. On the other hand, by optimizing a rib waveguide geometry for pumping in all-normal dispersion region, we are able to generate a smooth and flat-top coherent supercontinuum spectrum with a moderate bandwidth spanning the wavelength range 2–5.5 μ m with less than 5 dB spectral fluctuation over the entire output bandwidth. Our proposed design is highly suitable for making on-chip SC light sources for a variety of applications such as biomedical imaging, and environmental and industrial sensing in the mid-infrared region.